Changes to dietary and health outcomes following implementation of the 2012 updated US Department of Agriculture school nutrition standards: analysis using National Health and Nutrition Examination Survey, 2005–2016. Issue 16 (29th November 2020) - Jia, Jenny; Moore, Lynn L; Cabral, Howard; Hanchate, Amresh; LaRochelle, Marc R
Abstract: Objective: In 2012, the US government overhauled school nutrition standards, but few studies have evaluated the effects of these standards at the national level. The current study examines the impact of the updated school nutrition standards on dietary and health outcomes of schoolchildren in a nationally representative data set. Design: Difference-in-differences. We compared weekday fruit and vegetable intake between students with daily school lunch participation and students without school lunch participation before and after implementation of updated school nutrition standards using a multivariable linear regression model. Secondary outcomes included weekday solid fat and added sugar (SoFAS) intake and overweight and obesity prevalence. We adjusted analyses for demographic and family socio-economic factors. Setting: USA. Participants: K-12 students, aged 6–20 years ( n 9172), from the National Health and Nutrition Examination Survey, 2005–2016. Results: Implementation of updated school nutrition standards was not associated with a change in weekday fruit and vegetable intake ( β = 0·02 cups, 95 % CI −0·23, 0·26) for students with daily school lunch participation. However, implementation of the policy was associated with a 1·5 percentage point (95 % CI −3·0, −0·1) decline in weekday SoFAS intake and a 6·1 percentage point (95 % CI −12·1, −0·1) decline in overweight and obesity prevalence. Conclusions: Changes to US school nutrition standards were associated with reductions in the consumption of SoFAS as well as a decrease in overweight and obesity in children who eat school lunch. However, we did not detect a change in weekday intake of fruits and vegetables associated with the policy change.